A randomized trial comparing triiodothyronine (T3) with thyroxine (T4) for hemodynamically unstable brain‐dead organ donors. Issue 3 (12th February 2019) - Dhar, Rajat; Stahlschmidt, Emily; Yan, Yan; Marklin, Gary
Abstract: Rationale: Brain‐dead (BD) organ donors frequently exhibit hemodynamic instability and/or reversible cardiac dysfunction. Retrospective studies have suggested that thyroid hormone may stabilize hemodynamics and enhance myocardial recovery. Intravenous levothyroxine (T4) is most frequently utilized but studies have suggested that triiodothyronine (T3) may be superior. We performed a randomized comparative‐effectiveness trial to address this uncertainty in donor management. Methods: All heart‐eligible donors managed at a single OPO underwent standardized fluid resuscitation. If not weaned off vasopressors, donors underwent echocardiography (within 12 hours of BD) and were randomized to T3 or T4 infusion for eight hours. Results: A total of 37 BD donors were randomized (16 T3 vs 21 T4). Baseline ejection fraction (EF) was comparable (median 38% vs 45%, P = 0.87) as was vasopressor dosage (6 vs 12 μg/min of norepinephrine, NE, P = 0.12). Reduction in NE dose and proportion weaned off vasopressors was similar and LVEF improved in both groups (repeat EF: 50% vs 52.5%, P = 0.38) with almost half attaining EF ≥55%. Although more hearts were transplanted in the T3 group (10/16 vs 6/21, P = 0.04), this difference did not persist after adjusting for baseline imbalances in age and PF ratio. Conclusions: Infusion of T3 does not appear to confer significant hemodynamic or cardiac benefits over T4 for hemodynamic unstable BD organ donors.